Reestructuración técnico administrativa para la empresa Protucol P.V.C S.A.S. (2017)
The present work of degree was realized in the area of ​​production and in the administrative area of ​​the company study was carried out in the area of production and in the administrative area of the company. It was developed during a period of six months, in order to change the empirical method that is currently carried out where the main interest of the company has been to achieve Compliance in production and customer satisfaction, which has been affected by the internal structure of the company, without carrying out the documentation of processes, such as standardization and production capabilities, often generating a maximum effort Workers without taking into account their limitations.